A rare case of isolated gallbladder rupture following blunt abdominal trauma - Testini, Valentina; Tupputi, Umberto; Rutigliano, Claudia; Guerra, Francesco Saverio; Mannatrizio, Domenico; Bellitti, Roberto; Scarabino, Tommaso; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
Isolated gallbladder rupture are rare injuries. We present a case of gallbladder traumatic rupture in a 47-year-old patient involved in a motor vehicle collision, that presented abdominal pain with maximal intensity in the right upper quadrant.CT is the imaging technique of choice to diagnosis this entity, however the final diagnosis of gallbladder rupture is confirmed with laparoscopy. Cholecystectomy is the definitive treatment.